A Literature Review on First-Time Fathers: Factors Associated with Their Involvement in Infant Care and Implication for Counseling Practice - Harahap, Lena Susianti; Ginanjar, Adriana Soekandar (KONSELOR, 2025)
A first-time father faces numerous problems when his first child is born, including feelings of powerlessness, anxiety, and frustration. This depression will have a detrimental impact on both children's development, marital satisfaction, and family well-being. The stages of writing a narrative literature review based on the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) phases start from 1) selecting a review topic, 2) searching the literature, 3) collecting, reading, and analysing the literature, 4) writing the review, and 5) writing the reference list. This review included 13 research articles that fit the required inclusion criteria, i.e., articles on father participation, first-time father participants, and papers published between 2019 and 2024 retrieved from the Scopus database, Taylor & Francis Online, ProQuest, Sage Journals, and the Sinta platform from the Ministry of Education and Culture. We do not screen proceedings papers that are not peer-reviewed or published outside of 2019 and 2024. We excluded news pieces, literature reviews, book reviews, and popular articles from empirical or primary studies. Findings from this research review identified a range of factors associated with father involvement: 1) transition process, 2) emotional state, 3) self-efficacy, 4) depression, 5) social support, 6) role challenges, and 7) demographic characteristic. This study reveals that seven factors influence father involvement in infant care and have implications for counselling practice, e.g., PUSPAGA (Pusat Pembelajaran Keluarga or Family Learning Centre).  The majority of studies examined have concentrated on populations from Western cultures, with little consideration given to non-Western cultures, this study only addressing some Asian (e.g., Chinese, Thai, Korean, and Singaporean) and African cultures. Therefore, it is important to understand how different cultures influence father involvement, as the responses of fathers in a particular culture to their parental role cannot be generalised to all fathers from that cultural background.